Structural Characterization, Dft Calculation, Nci, Scan-Rate Analysis and Antifungal Activity Against Botrytis Cinerea of (E)-2-{[(2-Aminopyridin-2-Yl)Imino]-Methyl}-4,6-Di-Tert-Butylphenol (Pyridine Schiff Base) - Gacitua-Santalices, M; Gacitua-Santalices, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Botrytis cinerea is a ubiquitous necrotrophic filamentous fungal phytopathogen that lacks host specificity and can affect more than 1000 different plant species. In this work, we explored L1 [(E)-2-{[(2-aminopyridin-2-yl)imino]-methyl}-4,6-di-tert-butylphenol], a pyridine Schiff base harboring an intramolecular bond (IHB), regarding their antifungal activity against Botrytis cinerea. Moreover, we present a full characterization of the L1 by NMR and powder diffraction, as well as UV-vis, in the presence of previously untested different organic solvents. Complementary timedependent density functional theory (TD-DFT) calculations were performed, and the noncovalent interaction (NCI) index was determined. Moreover, we obtained a scan-rate study on cyclic voltammetry of L1. Finally, we tested the antifungal activity of L1 against two strains of Botrytis cinerea (B05.10, a standard laboratory strain; and A1, a wild type strains isolated from Chilean blueberries). We found that L1 acts as an efficient antifungal agent against Botrytis cinerea at 26 °C, even better than the commercial antifungal agent fenhexamid. Although the antifungal activity was also observed at 4 °C, the effect was less pronounced. These results show the high versatility of this kind of pyridine Schiff bases in biological applications. © 2020 MDPI AG. All rights reserved.